Digitalisasi Pembuatan Surat Keterangan Usaha Bagi Pelaku UMKM di Kelurahan Harapan Baru Kota Bekasi - Desmin Novita Sinaga; Reggya Ahmad Armansyah; Faustina Selly L.M.; Bintang Kurnia; Aristoteles; Rehan Surya Ardhana; Daniel Exaudi Gultom; Al Ihsan Fauzi Ardilla; Danu Righel Wibowo; Akhmad Dwi Purnomo; Alif Waskita Nugraha; Rangga Juniar Firzi; Tri Dharma Putra (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) conducted by students of Universitas Bhayangkara Jakarta Raya aims to support the digital transformation of public services in Kelurahan Harapan Baru, Bekasi City, particularly in the process of issuing Business Certificates (Surat Keterangan Usaha/SKU) for Micro, Small, and Medium Enterprises (MSMEs). Administrative services in the kelurahan were previously managed manually, resulting in slow processing times, data redundancy, and a high risk of human error. This program implemented a digital-based administrative service system utilizing Google Form for data input, Google Sheets as a database, and Google Apps Script for document automation. The implementation stages included initial coordination with the kelurahan, system design, internal testing, socialization, and direct assistance to MSME actors. The digital system enables faster SKU processing, structured data management, and improved accessibility for the community. The results indicate that the digital system significantly improves administrative efficiency, accuracy of data management, and transparency of public services. In addition, MSME actors gain easier access to business legality and increased digital literacy. This program demonstrates that simple and appropriate digital solutions can effectively support public service improvement and community empowerment at the village level.